Failure risk study of anchor bolts durability for loess slope under long-term hydro-thermal effect - Zhou Chang; Weifeng Sun; Changgen Yan; Hengxing Lan; Yuling Shi; Han Bao (Scientific Reports)
Abstract The long-term safety and durability of anchor systems are the focus of slope maintenance management and sustainable operation. This study presents the observed temperature, humidity, and anchor bolt stress at varying depths from four-year remote real-time monitoring of the selected loess highway cut-slope. The potential correlation between slope hydrothermal environment and anchor stress is analyzed. The anchor serviceability and durability were evaluated by establishing a time-dependent mathematical model of axial forces. The results show that the slope shallow loess exhibited hydro-thermal fluctuations annually during operation, subjecting the loess to continuous dry–wet cycles. Soil elastic deformation induces anchor axial force fluctuations due to hydro-thermo effects, while damage creep leads to the annual increase in axial force peaks and valleys. The increase in axial force is more significant at the upper slope and lower slope, thereby increasing the risk of retrogressive landslides in loess slopes. The time-dependent model of anchor axial force composing negative exponential and sine functions was proposed. The cyclic amplitudes, lower limits, and periods of temperature and humidity in slope can determine the model coefficients. The development patterns of axial force are classified into stable type, slow growth type, and accelerated growth type according to the characteristics of the model coefficients. Predicted results indicate that the anchor axial forces are lower than the landslide threshold within 30 years of slope operation, ensuring long safety and serviceability. Results provide a reference for the long-term safety evaluation and formulation of maintenance plans for loess slopes reinforced by anchor systems.